Synthesis of direct and indirect interplant water network - Chew, Irene Mei Leng (Animo Repository, 2008)
To date, most work on water network synthesis has been focusing on a single water network. The increase of public awareness toward industrial ecology has inspired new research into interplant water integration (IPWI). In this context, each water network may be grouped according to the geographical location of the water-using processes or as different plants operated by different business entities. Water source(s) from one network may be reused/recycled to sink(s) in another network. In this work, two different IPWI schemes, that is, "direct" and "indirect" integration are analyzed using mathematical optimization techniques. In the' former, water from different networks is integrated directly via cross-plant pipeline(s). A mixed integer linear program (MILP) model is formulated and solved to achieve a globally optimal solution. In the latter, water from different networks is integrated indirectly via a centralized utility hub. The centralized utility hub serves to collect and redistribute water to the individual plants, and may even function as a shared water regeneration unit. For the indirect integration scheme, a mixed integer nonlinear program (MINLP) is formulated and solved using a relaxation linearization technique to obtain an optimal solution. © 2008 American Chemical Society.